THE ROLE OF THE DANCE TEACHER IN DEVELOPING MOVEMENT CREATIVITY - FITRIANA EKA PUTRI; DWI KUSUMAWARDANI; KARTIAKA MUTIARA SARI (Journal of Dance and Dance Education Studies, 2024)
The research aims to describe the role of dance teachers in developing students' movement creativity in class XI dance learning at SMAN 1 Cikarang Barat. This research was conducted because of the conditions for teacher success in developing students' movement creativity in achieving dance work competence. The research methodology used is descriptive analysis, with a qualitative approach. The subject of this research is an arts and culture teacher at SMAN 1 Cikarang Barat. The results of the research showed that students obtained very good results in learning to create dance works. This is because teachers have 21 roles in dance learning. Dance teachers can carry out 15 roles in developing movement creativity optimally, namely the role of 1) educator; 2) teacher; 3) trainer; 4) reformer (innovator); 5) model and role model; 6) researcher; 7) activity driver; 8) view generator; 9) regular workers; 10) camp mover; 11) emancipator; 12) preservative; 13) learning resources; 14) motivator; 15) facilitator. Apart from that, dance teachers also act as 1) mentors, 2) managers; 3) demonstrators; 4) advisors; 5) evaluators; and 6) culminators, but these six roles have not been implemented optimally due to limitations in online learning and teacher consistency in preparing learning tools.